2017
DOI: 10.1016/j.carbon.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural prediction of graphitization and porosity in carbide-derived carbons

Abstract: Carbide-derived carbons (CDCs) are nanoporous carbons with a tunable pore size, making them desirable for their adsorption properties. Despite their applicability, reliable structural models are difficult to construct due to the interplay between strong short-range order and long-range disorder. Here, a mimetic methodology is developed to generate atomistic models of CDCs using Molecular Dynamics and the Environment Dependent Interaction Potential. This approach reproduces the main characteristics of experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 59 publications
(112 reference statements)
10
55
0
Order By: Relevance
“…Comparisons were made to an experimental carbide-derived carbon (CDC) material with similar structural properties. These models that use ReaxFF and employ a post-quenching compression step provide clear improvement upon prior CDC models generated using QMD in terms of local bonding and pore size distribution and also closely match those recently published using a process involving removal of metal atoms from a carbide and subsequent annealing [65].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Comparisons were made to an experimental carbide-derived carbon (CDC) material with similar structural properties. These models that use ReaxFF and employ a post-quenching compression step provide clear improvement upon prior CDC models generated using QMD in terms of local bonding and pore size distribution and also closely match those recently published using a process involving removal of metal atoms from a carbide and subsequent annealing [65].…”
Section: Discussionsupporting
confidence: 67%
“…Qualitative visual observations do not show any alterations of ring bonding. Thus, the combination of ReaxFF with a post-compression step results in pore size distributions that more closely match experiments as well as a recent study that generated CDCs using the EDIP force field and, rather than QMD, annealing of a system after removal of metal atoms from a carbide lattice [65]. Specifically, this compression step combines properties of QMD-generated models at different quench rates: the local bonding structure is dominated by six-membered rings, but the pore size distribution does not largely extend in the mesoporous regime.…”
Section: Qmd-generated Cdc Structuressupporting
confidence: 75%
See 1 more Smart Citation
“…Another convincing example showing a good agreement between TEM images and atomistic modelling of the structure for non-graphitising carbons is presented in Figure 27. It is clear that these models proposed by Tomas et al [60], optimized using an annealing based molecular dynamics approach, reproduce the main characteristics of HRTEM pictures including microstructure, porosity at the nanometre scale, and graphitisation with increasing temperature. Simultaneously, the authors showed that they reproduce features of the experimental pair distribution functions derived from XRD data [60].…”
Section: Glass-like Carbon and Other Pyrolysed Non-graphitising Carbonsmentioning
confidence: 97%
“…The issue of the sp 3 -bonds' presence in non-graphitising carbons has not been completely explained. Most recent studies using the total scattering method combined with computer simulations of the atomic structure support the thesis that these carbons contain mostly sp 2 -type bonds; however, the presence of small amounts of sp 3 bonds is possible [26,60]. It should be mentioned that so far, the TEM investigations have not provided images of diamond-like structures in non-graphitising carbons and observations of isolated sp 3 bonds would be extremely difficult.…”
Section: Glass-like Carbon and Other Pyrolysed Non-graphitising Carbonsmentioning
confidence: 99%